Biocontrol potential of Trichoderma-derived chitinase: optimization, purification, and antifungal activity against soilborne pathogens of apple - Akanksha; Sharma, Satish K.; Gupta, Bhupesh K.; Rana, Neerja; Sharma, Anju; Verma, Pramod (Frontiers in Fungal Biology, 2025)
Apple is most important fruit crop in Himachal Pradesh, contributing substantially to the state’s economy. However, soilborne diseases have emerged as a major concern affecting nursery-raised apples. Trichoderma species produce chitinase, an enzyme that degrades chitin, a major component of the fungal cell wall. This study aimed to optimize the growth parameters for chitinase production, extraction, purification, and characterization and to assess the antifungal potential against soilborne pathogens of apple. A total of 14 isolates of Trichoderma spp. produced chitinases in a colloidal chitin agar (CCA) medium to varying extents. The optimal incubation period, pH, substrate concentration, and incubation temperature were 7 days, 5, 1%, and 30°C, respectively, while the thermal and pH stability ranged from 30°C to 50°C and from 4 to 6, respectively. Chitinases were purified from Trichoderma atroviride UHFTA005 and UHFTA006 and from Trichoderma virens UHFTV017 with a molecular mass of 40 kDa. The chitinase from T. atroviride UHFTA005 at 0.60 μl inhibited the in vitro growth of Dematophora necatrix (92.22%) and Sclerotium rolfsii (91.11%). In a further in vivo evaluation of the chitinases, T. atroviride UHFTA005 was found to be more effective against white root rot and seedling blight of apple, with disease control of 86.67% and 73.33%, respectively, and with 86.67% white root rot disease control in nursery field conditions suggesting its strong potential as a biocontrol agent in nursery field conditions.